فانتازیا لە نۆڤلێتی: (حەسار و سەگەکانی باوکم )ی شێرزاد حەسەندا - حەسەن, پ.ی د. مەریوان عومەر (Sulaimani Journal for Humanities, 2021)
Novel or novelette, is one of the literature genres which involves in a long and deep storytelling. The story and picture of the main characters would be shown and illustrated from the perspective of the story teller in different shapes, incidents, positions, and time. Most of the time, fantasy would be seen as the basis of the events. As the result, we decided to focus and explore the fantasy in literature while researching on the worlds and genres of novel. Fantasy is seen as a work of art and literature in which it relies on a broad imagination, so it means that it is a widespread school of literature that covers most of the genres of literature. It is also a primary field of modern novel. In our research, the aim is to trigger the importance and the role of fantasy in Kurdish novels under the name of, Eaves and My Father's Dogs, which is a Fantasy Novelette written by the famous Kurdish author Sherzad Hassan. The research is composed of two main parts, conclusions and references part. First part is a theoretical section and composed of the below topics: ➤Fantasy's concept and definition ➤ Forms of fantasy Second part is a practical section which is the groundwork of our research, and we have a detailed and precise dialog on the reflection of fantasy in the novelette, Eaves and My Father's Dogs by Sherzad Hassan.